Problematic Mobile Phone Use and Life Satisfaction Among University Students During the COVID-19 Pandemic in Shanghai, China - Jiang, Wenning; Luo, Jin; Guan, Hannan; Jiang, Feng; Tang, Yi-Lang (Frontiers in Public Health, 2022)
Objective: This study examined problematic mobile phone use (PMPU) and its relationship with life satisfaction in Chinese university students during the pandemic. Methods: An anonymous online survey was conducted in a university in China. The Mobile Phone Addiction Index (MPAI) and the Satisfaction with Life Scale (SWLS) were used to assess the severity of problematic mobile phone use and life satisfaction, respectively. Data on demographic and health-related factors were also collected. Results: A total of 1491 undergraduate students (73.3% were male) completed the survey. On average, students in the survey reported spending 7.4±4.3 hours/day on phone use. Their MPAI score was 38.1±13.3 and SWLS score was 24.9±6.8, respectively. After controlling for confounding factors, the MPAI score was significantly associated with lower life satisfaction. Multiple linear regression revealed that higher monthly allowances, frequent insomnia, longer phone use duration were significantly associated with PMPU. Conclusion: University students in China spend nearly half of their waking hours on mobile phone, significantly longer than before the COVID-19 pandemic. PMPU is associated with insomnia, lower life satisfaction and higher allowances. If the trend continues after the pandemic, interventions may be needed. Increase in person interactions, limiting online social and gaming time, awareness campaign may be effective in reducing the impact of PMPU and improve life satisfaction.